DISTRIBUIÇÃO ESPACIAL, DINÂMICA E BIOMETRIA DE Campomanesia xanthocarpa (Mart.) O. Berg. EM FLORESTA OMBRÓFILA MISTA - Homczinski, Isabel (2017)
The objective of this research was to evaluate spatial distribution, dynamics and ecological interaction, as well as biometry, reproductive phenology and fruit yield of Campomanesia xanthocarpa (Mart.) O. Berg. - guabiroba, in a remnant of Mixed Ombrophilous Forest. The research was carried out in the Irati National Forest (Flona de Irati), which is located between the municipalities of Fernandes Pinheiro and Teixeira Soares, in the state of Paraná, Brazil. The data came from the continuous forest inventory carried out in permanent plots (25 ha) established in 2002, which is coordinated by professors of the Forest Management Laboratory of the State University of the Midwest, Campus de Irati, Paraná State, Brazil. For the analysis of the spatial distribution of the species the K function of Ripley was used. In the dynamics of the species, the phytosociology, mortality, ingrowth and increment (dbh and basal area) in 12 years of monitoring were analyzed, and the qualitative variables of the species (stem form, sociological position, plant health, form and position of the crown) were also evaluated. For the study of community phytosociology associated with C. xanthocarpa and interspecific ecological relation of the species, 92 plots of 0.04 ha were selected, with the tree of the species adopted as the center of the plot. In the analysis of the ecological interaction was used the sociability and competition indice of Glover and Hool and indice BAL. For the analysis of the biometric characterization of the species, its fruits, reproductive phenology and fruit yield estimation, 31 individuals were selected. The biometric variables of the tree were: total height, dbh, crown diameter and height. The study of phenological activity was divided into: early flowering (buds), anthesis (flower), immature and mature fruits. For the biometric characterization of the fruits were analyzed: length and width, fresh weight, number of seeds/ fruit and their volume. The productivity was estimated by the relation of the fruits by branches according to the number of branches per plant in general and in classes of DBH. The species presented an aggregate spatial distribution, with a total of 168 individuals having a density of seven ind.ha-1 and a basal area of 0.388 m².ha-1, with little variation between years, both in density and in the other parameters evaluated. In 12 years of monitoring the species presented an average annual rate of ingrowth and mortality of 1.53 and 0.63%, respectively, a common annual increment in diameter and basal area of 0.291 cm.year -1 and 0.0071 m². ha-1. year-1, respectively. In the community area associated with C. xanthocarpa were sampled in 2014, 96 tree species included in 65 genus and 38 families. The species with the highest value of importance within the community were: Araucaria angustifolia, Ilex paraguariensis, Ocotea porosa, Ocotea odorifera and Nectandra grandiflora, being these species the ones that are most associated and those that compete most with C. xanthocarpa. Regarding the biometry of C. xanthocarpa, the species presented mean values of total height, dbh, height and crown diameter of 14.2 m; 31.59 cm; 7.17 m and 9.44 m, respectively. As for the reproductive phenology, the species has seasonal phenology, with flowering in the months of September to October and fruiting in the months of October to December. The biometric characteristics of the fruits had mean values for width, length, fresh weight, seed / fruit number and volume of 22.01 mm; 19.74 mm; 6.64 g; 8 and 5.32 x 103 mm 3, respectively. The diametric class with the highest productivity was the dbh greater than or equal to 40 cm, and on average the species produces 1273 fruits, with an average weight of 8.64 kg.tree-1.